Analysis of The Cost of Production Target in PT Perkebunan Nusantara IV Unit Pabatu - Freddy Kancan Sembiring; Saipul Bahri Daulay; Sulastri Panggabean (Universitas Sumatera Utara, 2015)
The increase of production and quality of palm oil and palm kernel oil is strongly influenced by the production of fresh fruit bunches. Therefore, efforts are needed to increase the production of fresh fruit bunches. Pabatu estate is one of business unit of PT Perkebunan Nusantara IV that has head office in Medan, North Sumatera and engaged in the business of oil palm plantation and processing. The Study was aimed to analyze factors that influence the cost application in achieving production target, such as maintenance, premi harvest, security, and transportation. The factors were analized by Analythical Hierarchy Process (AHP) method. The results showed that maintenance cost was in first priority with the quality value of 0,4255. Security cost wast in the second priority with quality value of 0,2739. Harvest premi cost was in the third priority with quality value of 0,1613, and transportation cost was in the fourth priority with quality value of 0,1391, so that PT Perkebunan Nusantara IV Unit Pabatu should pay attention to maintenance cost in achieving production target Keywords: Analythical Hierarchy Process, Crude palm oil, Palm kernel oil, Fresh fruit bunch, Production system.